Estrategias didácticas para corregir la discalculia en el proceso de aprendizaje en el área de matemática de los niños y niñas de segundo grado del subnivel básica elemental, de la unidad educativa Graciela Atarihuana de Cueva, del cantón y provincia de Loja, periodo lectivo 2013-2014 - Procel Amay, Gabriela Fernanda (2015)
This research paper entitled: Teaching to correct dyscalculia in the learning process in the area of Mathematics children in second grade elementary basic sublevel, Graciela Education Unit Atarihuana of Cueva, canton and province of Strategies Loja, academic year 2013-2014 worked with the objective to determine the teaching strategies that help correct dyscalculia in the process of learning in the area of mathematics of children in second grade Basic sublevel Elementary Unit Educational Graciela Atarihuana de Cueva, the same that led to the development and implementation of strategies for teaching mathematics, for the realization of the research the following methods were used: Scientific; descriptive and analytic-synthetic, the same that were used throughout the research process, and on the analysis of empirical data, the same techniques were used as the survey, pretest and posttest for teacher and students the same as served for information on the difficulties related to the subject; for the analysis and interpretation of statistical to go elucidating the concerns disclosed both children and teachers, population consisted of 34 children and a teacher Of all the investigative work can manifest that the teacher knows of teaching strategies but the low educational material does not allow students to awaken interest, so I decided to work the curriculum by implementing strategies in the form of workshops.